Analysis of the Impact of Tax Policies on Foreign Direct Investment in Indonesia: A Case Study of the Manufacturing Sector - Nur Diana (Generasi Sains Indonesia, 2024)
This study examines the impact of tax policies on foreign direct investment (FDI) in Indonesia’s manufacturing sector, a strategic industry that plays a vital role in supporting national economic growth and industrial development. Recognizing the importance of fiscal policy as a determinant of investment climate, the research adopts a qualitative approach to provide an in-depth understanding of how tax regulations influence investor decisions. Data were collected through semi-structured interviews with key informants, including policymakers, tax practitioners, and industry representatives, as well as document analysis of relevant policy reports and regulatory frameworks. The findings reveal that tax policies significantly affect FDI inflows into Indonesia’s manufacturing sector. Incentives such as tax holidays, reduced corporate tax rates, and simplified administrative procedures were perceived as key factors in attracting investment, while frequent policy changes and regulatory uncertainties were identified as barriers to investor confidence. The study concludes that a stable, transparent, and competitive tax policy framework is essential not only for attracting new investors but also for retaining existing ones. Strengthening policy consistency and aligning tax regulations with long-term industrial goals are therefore critical strategies to enhance Indonesia’s competitiveness in the global investment landscape.